2012
DOI: 10.1021/jp3047054
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficiency of Graphene Nanosheets against Pathogenic Bacteria via Lipid Peroxidation

Abstract: Graphene nanosheets are highly recognized for their utility toward the development of biomedical device applications. The present study investigated the antibacterial efficiency of graphene nanosheets against four types of pathogenic bacteria. Graphene nanosheets are synthesized by a hydrothermal approach (under alkaline conditions using hydrazine hydrate). UV–vis and X-ray diffraction show a maximum absorbance at 267 nm and appearance of new broad diffraction peak at 26°, which ensures the reduction of graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
267
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(281 citation statements)
references
References 58 publications
11
267
0
Order By: Relevance
“…In other studies, lipid interaction was also proposed to be a major reason of the anti-microbial activity of graphene-based materials. 58,59 Li et al observed an edge-first uptake and internalization of graphene up to 10 μm lateral size by mammalian cells. After detailed molecular dynamics simulation, the authors proposed graphene entering into the lipid bilayer via corners or asperities (as opposed to enter via flat edges) to lower the energy barrier ( Figure 6C).…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…In other studies, lipid interaction was also proposed to be a major reason of the anti-microbial activity of graphene-based materials. 58,59 Li et al observed an edge-first uptake and internalization of graphene up to 10 μm lateral size by mammalian cells. After detailed molecular dynamics simulation, the authors proposed graphene entering into the lipid bilayer via corners or asperities (as opposed to enter via flat edges) to lower the energy barrier ( Figure 6C).…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…In general, bacterial deactivation can be the result of: 1) direct mechanical breakage of outer cell membranes by sharp edged nanoparticles (Akhavan and Ghaderi, 2010;Liu et al, 2009;Situ and Samia, 2014); 2) chemical oxidative stress mediated cell injury that is induced by in situ production of reactive oxygen species (Krishnamoorthy et al, 2012;Su et al, 2009); and 3) dehydration of cell membrane (Beney et al, 2004). It is highly likely that the latter two bacterial deactivation mechanisms are at play when wastewater is exposed to Fe 3+ -saturated montmorillonite.…”
Section: Spectroscopy Evidence Of Bacterial Cell Deactivation On Fe 3mentioning
confidence: 99%
“…Owing to nano-sizes, it may interfere with several chemical processes taking place in cells. Such interactions may cause oxidative stress leading to bacterial cell death [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%